Serum mast cell tryptase measurements: Sensitivity and specificity for a diagnosis of anaphylaxis in emergency department patients with shock or hypoxaemia. (2nd November 2017) - Francis, Abbie; Fatovich, Daniel M; Arendts, Glenn; Macdonald, Stephen PJ; Bosio, Erika; Nagree, Yusuf; Mitenko, Hugh MA; Brown, Simon GA
Abstract: Objective: Clinical diagnosis of anaphylaxis is principally based on symptoms and signs. However, particularly for patients with atypical symptoms, laboratory confirmation of anaphylaxis would be useful. This study investigated the utility of mast cell tryptase, an available clinical biomarker, for differentiating anaphylaxis from other causes of critical illness, which can also involve mast cell activation. Methods: Tryptase was measured (ImmunoCAP) in serum from patients with anaphylaxis and non‐anaphylactic critical illness (controls) at ED arrival, and after 1–2, 3–4 and 12–24 h. Differences in both peak and delta (difference between highest and lowest) tryptase concentrations between groups were investigated using linear regression models, and diagnostic ability was analysed using Receiver Operating Characteristic curve analysis. Results: Peak tryptase was fourfold (95% CI: 2.9, 5.5) higher in anaphylaxis patients ( n  = 67) than controls ( n  = 120) ( P  < 0.001). Delta‐tryptase was 5.1‐fold (95% CI: 2.9, 8.9) higher in anaphylaxis than controls ( P  < 0.001). Optimal test characteristics (sensitivity: 72% [95% CI: 59, 82] and specificity: 72% [95%CI: 63, 80]) were observed when peak tryptase concentrations were >11.4 ng/mL and/or delta‐tryptase ≥2.0 ng/mL. For hypotensive patients, peak tryptase >11.4 ng/mL had improved test characteristics (sensitivity: 85% [95% CI: 65, 96] and specificity: 92% [95% CI: 85, 97]); the use of delta‐tryptase reduced test specificity. Conclusion: While peak and delta tryptase concentrations were higher in anaphylaxis than other forms of critical illness, the test lacks sufficient sensitivity and specificity. Therefore, mast cell tryptase values alone cannot be used to establish the diagnosis of anaphylaxis in the ED. In particular, tryptase has limited utility for differentiating anaphylactic from non‐anaphylactic shock.